Promotion of Activated Carbon on the Nucleation and Growth Kinetics of Methane Hydrates - Zhang, Guodong; Shi, Xiaoyun; Zhang, Runcheng; Chao, Kun; Wang, Fei (Frontiers in Chemistry, 2020)
Due to the hybrid effect of physical adsorption and hydration, methane storage capacity in pre-adsorbed water activated carbon (PW-AC) under hydrate favorable conditions is impressive, and fast nucleation and growth kinetics are also anticipated, those fantastic natures suggest the PW-AC-based hydrates to be a promising alternative for methane storage and transportation. However, hydrate formation refers to multi-scale processes, the nucleation kinetics at molecule scale give rise to macro hydrate formation, and the presence of activated carbon (AC) causes this to be more complicated. Although adequate nucleation sites induced by abundant specific surface area and pore texture were reported to correspond to fast formation kinetics at macro perspective, the micro nature behind that is still ambiguous. Here, we evaluated how methane would be adsorbed on PW-AC under hydrate favorable conditions to improve the understanding of hydrate fast nucleation and growth kinetics. Micro bulges on AC surface were confirmed to provide numerous nucleation sites, suggesting the contribution of abundant specific surface area of AC to fast hydrate nucleation and growth kinetics. In addition, two-way convection of water and methane molecules in micro pores induced by methane physical adsorption further increases gas-liquid contact at molecular scale, which may constitute the nature of confinement effect of nano porespace.